Coordination chemistry of f-block metal ions with ligands bearing bio-relevant functional groups - Goetzke, Linda; Schaper, Gerrit; Maerz, Juliane; Kaden, Peter; Huittinen, Nina; Stumpf, Thorsten; Kammerlander, Kaitlin K. K.; Brunner, Eike; Hahn, Peter; Mehnert, Anne; Kersting, Berthold; Henle, Thomas; et al. (Coordination Chemistry Reviews, 2019)
Over recent decades there has been a great deal of interest and associated research into aspects of the f-block (lanthanide and actinide) metal chemistry of naturally-occurring ligands, such as proteins, peptides, porphyrins and related tetraaza derivatives as well as synthetically modified natural ligands and solely synthetic ligand systems incorporating bio-relevant functional groups. In this review, we present a wide-ranging overview of published work spanning the above areas, with emphasis on selected biological, medical and environmental aspects. Systems capable of discriminating between metal ions from within, or between, the lanthanide and actinide groups are also discussed including the design and synthesis of biomimetic radionuclide chelators and radionuclide decorporation agents as well as solid adsorbent materials for the uptake of radionuclides from the environment and elsewhere. Thus, the interaction of the f-group elements with a range of biopolymers, including systems based on cellulose, chitin, chitosan, humic substances as well as a range of synthetic model systems is also presented. Other applications include the synthesis of new luminescent materials, including luminescent probes and luminescent metal coordination polymers exhibiting unusual photophysical properties as well as systems showing potential for use in the development of new MRI imaging agents.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Actinides; Calix[4]arenes; Cellulose; Chitin; Chitosan; Humic substances; Lanthanides; Maillard products; Peptides; Porphyrins; Proteins; Siderophores